PENGARUH KUALIFIKASI KONTRAKTOR TERHADAP KUALITAS PEKERJAAN PROYEK KONSTRUKSI DI KABUPATEN TANAH DATAR - M.T., IPP, Ir. Surya Eka Priana, (Rang Teknik Journal, 2018)
AbstractIn the national development, the construction service industry has an important role in the countrys economy because it is able to contribute to gross domestic product of seven percent. Of the 98,000 existing contractors in Indonesia, 1% of them are large qualifications, 9% of middle qualifications and 90% of small qualifications, the increase in the number of companies has not been followed by improvements in their qualifications and performance, which can be seen from the quality of work, the timeliness of completion, and efficient utilization of personnel resources, capital, and technology in the implementation of construction services is not as expected. Based on the description above, then the formulation of the problem of this study are What factors affect the quality of contractor work in Tanah Datar regency and Analyze contractor qualification relationship with the quality of construction project work in Tanah Datar regency. The main factors affecting the quality of the contractors work are the human resource factors such as technical personnel who do not understand the technical specifications, working drawings and sufficient capital to finance the projects undertaken so that contractors experience financial difficulties when undertaking the project, in the filing of termin, the project capital obtained from bank loans, technical personnel understand the making of the report, the difficulty of putting STM and D3 engineering personnel, insuring the manpower, full-time technical personnel are always at the project site, technical personnel are placed the same as contract documents.Â Key Words : qualification, quality, construction